Attitudes and views on healthy lifestyle interventions for the prevention of dementia and cardiovascular disease among older people with low socioeconomic status: a qualitative study in the Netherlands. Issue 2 (28th February 2022) - Eggink, Esmé; Hafdi, Melanie; Hoevenaar-Blom, Marieke P; Richard, Edo; Moll van Charante, Eric P
Abstract : Objectives: Individuals with a low socioeconomic status (SES) have an increased risk of cardiovascular disease (CVD) and dementia, partly due to the high prevalence of unhealthy behaviours in this population. Interventions targeting lifestyle-related risk factors can potentially delay or prevent CVD and dementia onset. In this study, we explore the attitudes, experiences and views of low SES older adults on healthy lifestyles for the prevention of CVD and dementia. We also aim to study the potential role for coach-supported mobile health (mHealth) use, facilitating the development of the Prevention of Dementia using Mobile Phone Applications intervention. Design: We performed semi-structured interviews and used thematic analysis to analyse the data. Setting: Recruitment through multiple general practices in the Netherlands. Participants: Dutch non-demented adults aged ≥55, at increased risk of dementia, who possess a smartphone. Participants were purposively sampled on age, sex and history of CVD and diabetes. Results: Between May 2018 and June 2019, we performed 19 interviews. Five main themes were: (1) participants perceived little influence on their future health, (2) the sacrifices of healthy lifestyles outweighed the potential benefits, (3) physical complaints or disease could prompt behaviour change, (4) participants perceived they had limited self-efficacy to change their behaviour and (5) the social network had an important role in behaviour change. Needs regarding mHealth support were an easy-to-use smartphone application with trustworthy health information, which is provided in a non-obligatory way. Conclusions: Low SES older adults may benefit from lifestyle interventions that aim to improve self-efficacy levels by (remote) human support. Appropriateness and attractiveness of such interventions may increase when taking into account the participant's own autonomy, and when emphasising the direct gains of lifestyle changes for daily life. Moreover, involving the social network may be a valuable approach when developing lifestyle interventions for low SES older adults. Trial registration number: PRODEMOS trial, ISRCTN15986016 ; Pre-results.